Analysis of multi-service of public green spaces in rapidly growing Suburban areas in the Bangkok Metropolitan Region : a case of Rommani Thungsikan park in Donmueang District - Kulwadee Sujaritwong; Kim, Sohee Minsun; Vilas Nitivattananon; Lai Thi Phuoc Nguyen; Thailand (HM Queen) (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
Bangkok Metropolitan Region is mainly responsibility to at the local authority level responsible for the well-being of residents. Due to Bangkok is the capital of Thailand, Bangkok is the most population density and population growth as well as urbanization, especially in outer area of BMR and peri-urban areas. These processes related to human demands of population in the city that caused people seek to exposure natural environment, including green spaces for recreation. This study emphasized on park service and facility which are the benefits for people who access the public green space (PGS) in order to study services and benefits of PGS to the large public in suburban area. A multi-service framework was developed with ecosystem services and social benefits of PGS for assessing user's satisfaction on using the PGS services that the park can provide the services and benefits to human needs. Questionnaire survey, pilot observation, in-depth interview were used for primary data collection, together with collecting available secondary data. One hundred thirty three were surveyed with park users, and then analyzed statistically. Satisfaction analysis on multi-service ofPGS was also used in analyzing PGS management process and developing recommendations. As a result of the study find that most of park users at Rommani Thungsikan Park was satisfied at high level on existing multi-service ofPGS following four services: (1) comfort and image, (2) access and linkage, (3) use and activity, and (4) sociability. There is only social support network of users' personal characteristic affects to user satisfaction on multi- service ofPGS. Moreover, some kinds of purpose that people would like to enjoy doing can affect to satisfaction on PGS services. In term of PGS management analysis, the studied results found that Rommani Thungsikan Park has the multi-service that PGS should provide to people. This study suggest the developmental practices to park office for services' quality inside the park that can be involved the user needs on environmental benefits .. For further study, people participation on management of cleanness of PGS is recommended consider towards to conservation of natural environment and sustainable development.
A thesis in partial fulfillment of the requirements for the degree of Master of science in Urban Environmental Management
Thesis (M. Sc.) - Asian Institute of Technology, 2018
Keywords: Public spaces -- Thailand -- Bangkok; Urban ecology -- Thailand -- Bangkok